2021
DOI: 10.3390/nu13072343
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with Ischemic and Hemorrhagic Stroke

Abstract: Data on the association between body mass index (BMI) and stroke are scarce. We aimed to examine the association between BMI and incident stroke (ischemic or hemorrhagic) and to clarify the relationship between underweight, overweight, and obesity and stroke risk stratified by sex. We analyzed the JMDC Claims Database between January 2005 and April 2020 including 2,740,778 healthy individuals (Median (interquartile) age, 45 (38–53) years; 56.2% men; median (interquartile) BMI, 22.3 (20.2–24.8) kg/m2). None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…Além disso, o baixo peso, o excesso de peso e a obesidade foram associados a maior risco de AVC hemorrágico em homens, contudo, a relação AVCmortalidade é mais explorada em relação ao IMC, do que a CB. 18,19 Os valores obtidos de PCR (Proteína C Reativa) dos pacientes na tabela 3, demonstram que a maioria dos enfermos está com risco cardiovascular elevado. Um estudo demonstrou que níveis plasmáticos elevados de proteína C reativa ultrassensível (PCR-us) na admissão estão associados com deterioração neurológica e piora no desfecho de pacientes com AVC isquêmico.…”
Section: Santos If Et Al/ Revista De Ensino Ciência E Inovação Em Saú...unclassified
“…Além disso, o baixo peso, o excesso de peso e a obesidade foram associados a maior risco de AVC hemorrágico em homens, contudo, a relação AVCmortalidade é mais explorada em relação ao IMC, do que a CB. 18,19 Os valores obtidos de PCR (Proteína C Reativa) dos pacientes na tabela 3, demonstram que a maioria dos enfermos está com risco cardiovascular elevado. Um estudo demonstrou que níveis plasmáticos elevados de proteína C reativa ultrassensível (PCR-us) na admissão estão associados com deterioração neurológica e piora no desfecho de pacientes com AVC isquêmico.…”
Section: Santos If Et Al/ Revista De Ensino Ciência E Inovação Em Saú...unclassified
“…As already stated, obesity is considered a risk factor for many diseases, including cardiovascular and cerebrovascular diseases [ 13 16 ]. It is also found that the risk of perioperative mortality is increased among obese patients undergoing vascular surgery [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many findings in the past suggesting that elevated BMI is associated with a higher risk of ischemic stroke (36)(37)(38)(39). However, the relationship between BMI and the prognosis of stroke patients is uncertain and controversial.…”
Section: Discussionmentioning
confidence: 99%